Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1523/jneurosci.0678-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessels Form a Scaffold for Neuroblast Migration in the Adult Olfactory Bulb

Abstract: New cells are continuously added to the rodent olfactory bulb (OB), throughout development and in adults. These cells migrate tangentially from the subventricular zone along the rostral migratory stream to the OB, where they migrate radically from the center to periphery of the OB. Although different modalities of radial migration have been described in other brain regions, the mechanisms governing radial migration in the OB are still mostly unknown. Here, we identify a new modality of migration in which neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
166
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(180 citation statements)
references
References 26 publications
7
166
1
Order By: Relevance
“…The tortuous paths of multipolar cells could be indicative of migration along blood vessels, which serve as a scaffold for migrating neurons in other regions of the brain (Bovetti et al, 2007). We therefore compared the migration paths of 11 multipolar GFP ϩ cells with the pattern of blood vessels ( Fig.…”
Section: Migratory Behavior Of New Neurons In Vivomentioning
confidence: 99%
“…The tortuous paths of multipolar cells could be indicative of migration along blood vessels, which serve as a scaffold for migrating neurons in other regions of the brain (Bovetti et al, 2007). We therefore compared the migration paths of 11 multipolar GFP ϩ cells with the pattern of blood vessels ( Fig.…”
Section: Migratory Behavior Of New Neurons In Vivomentioning
confidence: 99%
“…Real-time video-imaging experiments of cell migration in slices of the adult mouse forebrain showed that neuroblasts migrate close to the blood vessels with their soma and leading process (Snapyan et al 2009). Once in the OB, a subset of these newly arrived olfactory neuron precursors follow a vasophilic migration around radial blood vessels to cross the granule cell layer toward the periphery of the OB (Bovetti et al 2007). ECs of the RMS synthesize brain-derived neurotrophic factor (BDNF), which fosters neuronal migration via p75NTR expressed on neuroblasts (Snapyan et al 2009).…”
Section: Blood Vessels Guide Axon Outgrowth and Neuronal Migrationmentioning
confidence: 99%
“…In those first weeks the glial processes of astrocytes form a relative homogeneous network through which tangential migration occurs (Peretto et al, 1997(Peretto et al, , 1999. Once migrating cells reach the OB, they detach from chains and migrate radially along blood vessels (Bovetti et al, 2007b) to reach their final destination in the glomerular (Gl) and granule cell layer (Gcl) where most of them differentiate into interneurons (Luskin, 1993). Previous studies from our and other groups, reported that in rodents the average speed of adult tangential and radial neuroblast migration range from 20 to 40 μm/h and consists of cycles of higher speed advancement interspersed with stationary/slower periods (Bovetti et al, 2007a;Lois and Alvarez-Buylla, 1994;Luskin and Boone, 1994).…”
Section: Migrationmentioning
confidence: 99%
“…Conversely, antagonistmediated inhibition of Glu K5 -containing kainate receptor but not of the metabotropic mGluR5 receptor, increases the speed of neuronal migration (Platel et al, 2008b). Using time-lapse confocal microscopy on fluorescently labeled neuroblasts in acute brain slices (Bovetti et al, 2007a;Bovetti et al, 2007b;De Marchis S. et al, 2001), we also analyzed the involvement of GABA and glutamate receptors in neuroblast tangential migration along the RMS, both in early postnatal period (P5, when chain migration does not occur yet) and in young-adult mice (P21) when glial tube are formed . Application of the GABA A antagonist gabazine (10 μM) on acute brain slices, increases the migration rate by 50% and 45% in P5 and P21 mice respectively, while GABA A agonist muscimol (10 μM) decreases neuronal precursor speed by 30% (P5) and 40% (P21) ( Fig.…”
Section: Amino Acids: Gaba and Glutamatementioning
confidence: 99%